2019
DOI: 10.1002/pi.5887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the annealing procedure and the molecular weight on the crystalline phase morphology and thermal properties of polylactide

Abstract: The thermomechanical properties of poly(lactide) (PLA) are strongly related to its semicrystalline microstructure and morphology. Thermal annealing is a strategy to improve the crystallinity of PLA. However, the different techniques and specimen types needed for each kind of characterization could lead to misleading conclusions. In this work, annealed samples of three PLA grades with different molecular weights were studied by DSC, wide angle X‐ray scattering and polarized optical microscopy (POM) and the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…An endothermic shoulder peak before the melting peak was observed. This shoulder peak can be considered to be related to the α ′ to α phase transition, and the main peak is thought to be the melting of α form 33,34 . Compared with the annealed one, this shoulder peak increased to a higher temperature and became less pronounced.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An endothermic shoulder peak before the melting peak was observed. This shoulder peak can be considered to be related to the α ′ to α phase transition, and the main peak is thought to be the melting of α form 33,34 . Compared with the annealed one, this shoulder peak increased to a higher temperature and became less pronounced.…”
Section: Resultsmentioning
confidence: 97%
“…This shoulder peak can be considered to be related to the α 0 to α phase transition, and the main peak is thought to be the melting of α form. 33,34 Compared with the annealed one, this shoulder peak increased to a higher temperature and became less pronounced. The melting temperature (T m ) shifted slightly to a higher temperature.…”
Section: Thermal Propertymentioning
confidence: 88%
“… 32 Similar trend was observed for high molecular weight semicrystalline PLLA, which exhibited limited crystallisation due to high density of chains entanglement presented lower chain mobility. 38 Authors suggested that, the lower the molecular weight was, the higher the crystallisation rate of PLLA. Under an annealing process, chain mobility increased with temperature resulting in an increase of crystallinity (PCL45w, PCL80w).…”
Section: Discussionmentioning
confidence: 99%